2020
DOI: 10.3390/medicina56110616
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Antigen 50: Values for Diagnosis and Prognostic Prediction of Intrahepatic Cholangiocarcinoma

Abstract: Background and objectives: Cancer-associated carbohydrate antigen 50 (CA50) is a marker for detection of gastrointestinal cancers, especially of pancreatic and colon cancer. In this study, the power of CA50 as a diagnostic and prognostic marker was evaluated in intrahepatic cholangiocarcinoma (iCCA). Materials and Methods: Serum CA50 levels of iCCA patients and non-cholangiocarcinoma controls (non-CCA, including healthy persons and patients with benign biliary diseases and other gastrointestinal cancers) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“… 42 The elevated levels of CA50 in patients with intrahepatic cholangiocarcinoma suggest that the expression of CA50 may help distinguish between benign and malignant bile duct diseases. 43 It has been reported that the level of serum tumor marker CA50 can serve as an auxiliary indicator for diagnosing early pancreatic ductal adenocarcinoma, which is of great significance for improving the diagnostic sensitivity and accuracy of early pancreatic ductal adenocarcinoma. 44 The high levels of serum CA50 detected in patients with colorectal cancer can be used to assist in monitoring disease recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“… 42 The elevated levels of CA50 in patients with intrahepatic cholangiocarcinoma suggest that the expression of CA50 may help distinguish between benign and malignant bile duct diseases. 43 It has been reported that the level of serum tumor marker CA50 can serve as an auxiliary indicator for diagnosing early pancreatic ductal adenocarcinoma, which is of great significance for improving the diagnostic sensitivity and accuracy of early pancreatic ductal adenocarcinoma. 44 The high levels of serum CA50 detected in patients with colorectal cancer can be used to assist in monitoring disease recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, serum levels of CA50 taken from 85 patients with iCCA were compared to healthy individuals (n=110), patients with benign biliary disorders (n = 23) and other cancers (n = 33). CA50 levels differentiated iCCA from non-CCA cases with 65.9% sensitivity and 87.3% specificity (AUC = 0.806) ( 130 ).…”
Section: Diagnostic and Prognostic Biomarkers In Ccamentioning
confidence: 99%
“… 15 , 16 , 17 , 18 Despite extensive research on the screening and diagnostic value of CA50, its powerful evidence and data in BTC or CHC patients have rarely been explored. 19 , 20 To date, the exact clinical value of CA50 in BTCs remains unclear. Whether CA50 was more effective in combination with other tumor markers was also unclear.…”
Section: Introductionmentioning
confidence: 99%